2010
DOI: 10.1890/09-1051.1
|View full text |Cite
|
Sign up to set email alerts
|

Conserving biodiversity in production landscapes

Abstract: Alternative land uses make different contributions to the conservation of biodiversity and have different implementation and management costs. Conservation planning analyses to date have generally assumed that land is either protected or unprotected, and that the unprotected portion does not contribute to conservation goals. We develop and apply a new planning approach that explicitly accounts for the contribution of a diverse range of land uses to achieving conservation goals. Using East Kalimantan (Indonesia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
77
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(80 citation statements)
references
References 58 publications
2
77
0
1
Order By: Relevance
“…Only recently, however, did investigation into systematic zoning begin (Moilanen et al 2005) enabling planning for multi-objective, multistakeholder contexts (Wilson et al 2010). Forest managers used simulated annealing to harmonize site suitability and different forestry regimes (Bos 1993) and Verdiell & Sabatini (2005) Sabatini & Verdiell (2007 internally zoned a protected area designated as a world heritage site in Argentina.…”
Section: Zoning In the Context Of Systematic Conservation Planningmentioning
confidence: 99%
See 2 more Smart Citations
“…Only recently, however, did investigation into systematic zoning begin (Moilanen et al 2005) enabling planning for multi-objective, multistakeholder contexts (Wilson et al 2010). Forest managers used simulated annealing to harmonize site suitability and different forestry regimes (Bos 1993) and Verdiell & Sabatini (2005) Sabatini & Verdiell (2007 internally zoned a protected area designated as a world heritage site in Argentina.…”
Section: Zoning In the Context Of Systematic Conservation Planningmentioning
confidence: 99%
“…Howevers in both cases, the claims of spatially explicit zoning were based only on spatial attributes such as compatibility and connectivity. They overlooked the explicit incorporation of objectives in the optimization, failing to explicitly target representation, complementarity and constraints of conflicting objectives in the actual problem definition (Possingham 2001;Wilson et al 2010).…”
Section: Zoning In the Context Of Systematic Conservation Planningmentioning
confidence: 99%
See 1 more Smart Citation
“…The focus of conservation planning is shifting from solely prioritising for protected areas, and towards new objectives of identifying areas for targeted management to ameliorate negative impacts and to improve ecosystem health (Budiharta et al, 2014;Moilanen et al, 2011;Wilson et al, 2010). This includes targeting control of invasive species (Auerbach et al, 2014;Evans et al, 2011), reduction of poaching (Plumptre et al, 2014), or management of fire (Richards et al, 1999;Wilson et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…These advances have facilitated more complex approaches to systematic conservation planning that support more holistic spatial approaches in which multiple uses are considered and planned for explicitly. Studies that consider multiple land uses have demonstrated that potential conflicts can be minimized by explicitly accounting for associated trade-offs (Polasky et al 2005, Wilson et al 2010, Venter et al 2013). …”
Section: Introductionmentioning
confidence: 99%